Characterization of protein glycosylation in Francisella tularensis subsp. holarctica: identification of a novel glycosylated lipoprotein required for virulence - Balonova, Lucie; Mann, Benjamin F; Cerveny, Lukas; Alley, William R; Chovancova, Eva; Forslund, Anna-Lena; Salomonsson, Emelie N; Forsberg, Ake; Damborsky, Jiri; Novotny, Milos V; Hernychova, Lenka; Stulik, Jiri (Molecular & cellular proteomics, 2012)
FTH_0069 is a previously uncharacterized strongly immunoreactive protein that has been proposed to be a novel virulence factor in Francisella tularensis. Here, the glycan structure modifying two C-terminal peptides of FTH_0069 was identified utilizing high resolution, high mass accuracy mass spectrometry, combined with in-source CID tandem MS experiments. The glycan observed at m/z 1156 was determined to be a hexasaccharide, consisting of two hexoses, three N-acetylhexosamines, and an unknown monosaccharide containing a phosphate group. The monosaccharide sequence of the glycan is tentatively proposed as X-P-HexNAc-HexNAc-Hex-Hex-HexNAc, where X denotes the unknown monosaccharide. The glycan is identical to that of DsbA glycoprotein, as well as to one of the multiple glycan structures modifying the type IV pilin PilA, suggesting a common biosynthetic pathway for the protein modification. Here, we demonstrate that the glycosylation of FTH_0069, DsbA, and PilA was affected in an isogenic mutant with a disrupted wbtDEF gene cluster encoding O-antigen synthesis and in a mutant with a deleted pglA gene encoding pilin oligosaccharyltransferase PglA. Based on our findings, we propose that PglA is involved in both pilin and general F. tularensis protein glycosylation, and we further suggest an inter-relationship between the O-antigen and the glycan synthesis in the early steps in their biosynthetic pathways.
Keywords: Molecular Sequence Data; sekvence aminokyselin; Virulence Factors; proteiny fimbrií; O-antigeny; sacharidové sekvence; multigenová rodina; O Antigens; mutace; Francisella tularensis; glykosylace; Multigene Family; Glycosylation; Mutation; Fimbriae Proteins; Amino Acid Sequence; Tandem Mass Spectrometry; tandemová hmotnostní spektrometrie; molekulární sekvence - údaje; Carbohydrate Sequence; faktory virulence